Extremity Strengthening Exercise on Neonates Receiving Phototherapy - Rahmawati, Eni; Susmarini, Dian; Purnamasari, Meivita Dewi (Jurusan Keperawatan FIKES UNSOED, 2020)
Neonatal jaundice is a clinical condition in infants characterized by yellow staining of the skin and sclera due to the accumulation of unconjugated bilirubin excess. This is the leading cause of deathin 60% -80% of newborns. This research was aimed to investigate the effects of exercise on neonates with nutritional status and vital signs who were receiving phototherapy. In this quasi experimental study, 34 full term neonates with jaundice admitted for phototherapy were selected through quota sampling. Subjects were assigned to exercise and control groups. Neonates in exercise group received a passive extremities exercise for 15 to 20 minutes on extremities twice a day for 3 days, while the control group did not received any exercise. Statistics analysis used independent t test and mann-whitney test. Demographic and clinical characteristics, the defecation frequency, vital sign, total feeding amount and body weight were identified and compared between two groups.On the third day, the exercise group showed a significantly higher defecation frequency (p=0.000) and significant in respiration rate (p=0.029); not significant in vital signs (heart rate p=0.583 and temperature p=0.807;) enteral feeding (p=0.202) and body weight (p=0.181). Exercise could increase defecation frequency in neonates with jaundice receiving phototherapy.The effect of exercise was limited to stabilize temperature and heart rate.